UPAYA PENINGKATAN AKTIVITAS BELAJAR SISTEM HIDROLIK MELALUI METODE JIGSAW LEARNING PADA SISWA KELAS X TKR 1 SMK MUHAMMADIYAH KARANGMOJO KABUPATEN GUNUNGKIDUL - Muslimin Annas; Pairun Roniwijaya (Universitas Sarjanawiyata Tamansiswa, 2014)
This study aims to improve the learning activity through the hydraulic system of Jigsaw Learning method in class X TKR SMK Muhammadiyah 1 KarangmojoThis study is an action research (PTK). The subjects were students of class X of SMK Muhammadiyah 1 Karangmojo TKR. Data was collected through observation, interviews, field notes, and nontes testing, documentation, and analysis of documents. This study consisted of three cycles. Each cycle consists of four stages, namely (1) the action plan; (2) the implementation of the action; (3) observation; and (4) reflection and revision. Data analysis was performed by descriptive qualitative and quantitative skills is to describe the hydraulic system before and after the implementation of the action. The validity of the data obtained through validity (the validity of the results, the validity of the process, the validity of the dialogic, democratic validity) and reliability.The results showed that there is an increase in the hydraulic system of learning activities in class class X TKR SMK Muhammadiyah 1 Karangmojo through Learning through Jigsaw method. This increase is reflected by an increase in the quality of the process and outcomes of learning activities hydraulic system. The increase reflected the quality of the increasing activity of students during the lesson. Improved quality of results reflected increased average value of the hydraulic system of students' learning activities before and after the action. Average ability of students before and after the action was 63.33 subject to measures for cycle three times the average value of students rose to 78.93. This shows that there has been growing positive attitude in students' learning activities so that the ability of the hydraulic system began to increase. Hydraulic system enhancements increase of 15.6 or 24.63%.